A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus - Meneghetti, Jéssica; Takiya, Daniela Maeda; Paladini, Andressa (Zootaxa, 2019)
A new species of Ferorhinella Carvalho & Webb 2004 from southeastern Brazil is described and illustrated, and a taxonomic key to species in the genus is provided. Ferorhinella itatiaiensis sp. nov. can be distinguished from other known species of the genus mainly by the paramere with rounded apex and two subapical lateral spines on outer surface, one long, dorsally inserted and the other one small, ventrally inserted; and dorsal margin of the subgenital plates with a rectangular elevation, covered with small, tooth-like spines.